Social indicator of unpaid work in Brazil: A methodological proposal - Lucilene Morandi; Hildete Pereira de Melo (Atlantic Review of Economics (ARoEc), 2020)
Women are largely responsible for reproductive work of human life. Perhaps this is why they are also historically and socially responsible for the housework and care of other family members. This work that is freely provided to the family, mostly by women and to a lesser extent by men, is called unpaid work. Unpaid work, in addition to improving the well-being of the family, is fundamental to the functioning of society, as it ensures the availability of labor force for the paid labor market. Nonetheless, unpaid work and all its production of goods and services is invisible to the society. This is because most countries do not have official statistics on this production. Some statistics already available show that unpaid work generates goods and services that account for about 13 to 30% of GDP. Moreover, since women mostly perform this work, the time spent on these activities impacts women's participation in the paid labor market and, consequently, their income. Among the United Nations Millennium Development Goals for reducing inequality is the measurement of unpaid work through a Satellite Account in order to make it visible and its importance recognized by society. This study proposes the discussion of a social indicator of unpaid work for Brazil. To this end, it develops a methodological proposal to estimate a Satellite Account of Unpaid Work to be incorporated into National Accounts, emphasizing the importance of this statistic for defining more efficient and fairer public policies to reduce inequality.
Keywords: E01; E24; 330; Satellite Accounts (GDP); Sexual division of work; Labor market; Gender and macroeconomics